2013
DOI: 10.1088/1742-6596/442/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

"Systemic nonlocality" from changing constraints on sub-quantum kinematics

Abstract: In a new approach to explain double-slit interference "from the single particle perspective"via "systemic nonlocality", we answer the question of how a particle going through one slit can "know" about the state of the other slit. We show that this comes about by changed constraints on assumed classical sub-quantum currents, which we have recently employed [1] to derive probability distributions and Bohm-type trajectories in standard double-slit interference on the basis of a modern, 21 st century classical phy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Similarly in quantum phenomena which we observe and create there should be something behind the scenes which is causally responsible for outcomes we register. In our opinion quantum probabilities neither correspond to irreducible propensities of individual physical systems nor to beliefs of some human agents but they are objective properties of quantum phenomena as a whole [4,5,31,37,67,68,70]. Necessity of probabilistic description is due to the lack of control on what is going behind the scenes.…”
Section: Physical Realitymentioning
confidence: 97%
“…Similarly in quantum phenomena which we observe and create there should be something behind the scenes which is causally responsible for outcomes we register. In our opinion quantum probabilities neither correspond to irreducible propensities of individual physical systems nor to beliefs of some human agents but they are objective properties of quantum phenomena as a whole [4,5,31,37,67,68,70]. Necessity of probabilistic description is due to the lack of control on what is going behind the scenes.…”
Section: Physical Realitymentioning
confidence: 97%
“…As there is no additional force on the particle, we do not speak of a "dynamical" nonlocality, but of a "systemic" one instead. For more details, see [27].…”
Section: "Systemic" Nonlocality In Double Slit Interferencementioning
confidence: 99%
“…The authors show within the Heisenberg picture that the opening or closing of a slit results in the nonlocal transfer of (what they call "modular") momentum. (Our group has shown that this effect can also be demonstrated when using the Schrödinger picture [15]. )…”
Section: Nonlocality and Relativity: A Case For Lorentz Invariant Supmentioning
confidence: 88%